Seismic anisotropy of serpentinite from Val Malenco, Italy. Issue 6 (22nd June 2015) - Kern, Hartmut; Lokajicek, Tomas; Svitek, Tomas; Wenk, Hans‐Rudolf
Abstract: Serpentinites, deformed in mantle subduction zones, are thought to contribute significantly to seismic anisotropy of the upper mantle and have therefore been of great interest with studies on deformation, preferred orientation, and elastic properties. Here we present a combined study of a classical sample from Val Malenco, Italy, investigating the microstructure and texture with state‐of‐the art synchrotron X‐ray and neutron diffraction methods and measuring ultrasonic velocities both with a multi‐anvil apparatus and a novel instrument to measure 3‐D velocities on spheres. Both, results from diffraction methods and velocity measurements are compared, discussing advantages and disadvantages. From spherical velocities, elastic tensor properties can be derived by inversion. Also from quantitative texture measurements, elastic properties can be modeled by self‐consistent averaging. Good agreement between the velocity and microstructural models is observed. Key Points: Elastic anisotropy of serpentinite Acoustic wave velocity measurements Crystal preferred orientation